Quality Enhancement with Maximum Allowable p-Cycle Length and with m-Cycle in Optical Mesh Networks - Chandra Jaiswal, Deo; Asthana, Rachna (International Journal of Engineering and Technology, 2018)
In the modern age, fast communication of information is an essential requirement of everyone moreover communication between long distances is mainly provided by optical mesh networks.  Network failures of small interval lead to large disruptions in providing service of transferring of data. Therefore, for uninterrupted network services, network survivability plays a vital role. Preconfigured protection cycle (p-cycle) combines the advantages of the capacity efficiency of mesh as well as a fast restoration speed of ring based protection schemes which are two fundamental techniques of network survivability. Level of optimal redundancy is assured by selecting Hamiltonian p-cycle as it passes through all the nodes of the network. Obviously, the restored path length will be increased due to increased p-cycle length that increases the excessive signal degradation and propagation delay which results in decreased level of quality of service (QoS). Priority-based traffic in an optical mesh network can be restored with different levels of QoS. So the maximum p-cycle length is made definite up to a certain limit, the lower limit for premium-grade and the upper limit for low-grade traffic is done. The concept of shortest path routing (SPR) is commonly referred in the optical networks with the condition of p-cycle length limit when link failure takes place. Monitoring cycle (m-cycle) is responsible for fault detection and localization before p-cycle protection. In this paper, dynamic path routing (DPR) with maximum p-cycle length limitation including m-cycle and SPR with only p-cycle length limit is compared. An Integer Linear Programme (ILP) is developed to minimize spare capacity for DPR with the maximum p-cycle length limit along with m-cycle against single link failure. The result of this programme illustrates that DPR with maximum p-cycle length limitation and m-cycle requires fewer total spare capacity in comparison with SPR where the only length of p-cycle is limited and monitoring is not taken in to account.